Pengaruh Konsentrasi ekstrak Air dan etanol Kulit Batang Azadirachta Indica Terhadap Penghambatan Pertumbuhan Streptococcus Mutans - Sunarintyas, Siti (Fakultas Kedokteran Gigi Universitas Trisakti, 2008)
Neem (Azadirachta indica) is a medicinal plant. The stem bark of Azadirachta indica contains component of polyphenol and alkaloid that have been proven to exhibit antibacterial properties. This study aimed to determine the influence of aqueous and ethanolic Azadirachta indica stem bark extract concentration in inhibiting the growth of Streptococcus mutans. Two different Azadirachta indica stem bark extracts, aqueous and ethanolic extracts, were prepared at 0.5, 1.2, and 4% (w/v: extraction powder/water) respectively. Fifty micro litters of each extracts were dropped on MHA (Muller Hinton Agar) that had been inoculated with Streptococcus mutans of 108 CFU/ml. After 24 hours of incubation, the inhibition diameters were measured by sliding caliper. The data were analyzed by analysis of varian (ANOVA) followed by Least Significant Difference (LSD). The result showed that there were significant difference of the extraction methods (p<0.001), Azadirachta indica concentrations (p<0.001), and the extraction methods-concentrations (p<0.001) on the inhibition growth of Streptococcus mutans. In conclusion, aqueous and ethanolic Azadirachta indica stem bark extract concentration influenced the inhibition growth of Streptococcus mutans. Ethanolic Azadirachta indica stem bark extract had higher inhibition growth on Streptococcus mutans than the aqueous one.